Experimental Investigation of the Deformation Characteristics of Tianjin Clays under Coupled Dynamic Stress and Seepage Fields - Huayang Lei; Shuangxi Feng; Rui Jia; Mingjing Jiang (Advances in Civil Engineering)
The causes, prevention, and control of clay disasters are of great concern in practical engineering applications. Recently, due to unprecedented economic development, increasing numbers of tunnels and subgrades of tidal flat areas have been built in Tianjin, China. Soft soil ground not only bears the vibration load during operation and construction but also receives seepage effects caused by the bursting of pipelines and variations in groundwater levels. Under the coupling action of dynamic and seepage loads, large settlement can occur in soft soil since the deformation is related to both cyclic stress and seepage. Therefore, it is significant to understand the dynamic deformation characteristics of soil to ensure the safety of engineering applications. In this study, a series of laboratory cyclic triaxial tests were conducted to study the deformation behaviours of Tianjin clays under coupled cyclic stress and seepage fields. To simulate the seepage field, water pressure is applied at the bottom of the specimen, and the water can be drained from the top of the specimen to form a head difference in the specimen during the tests. The effects of the seepage pressure, cyclic stress ratio (CSR), and a number of cycles (N) on the hydraulic conductivity, axial deformation, hysteresis curve and dynamic modulus of Tianjin clays were systematically investigated. The laboratory results show that the hydraulic conductivity (k) decreases with the increasing seepage pressure, CSR, and N, and its range is from 4.6 × 10−8 cm/s to 7.4 × 10−8 cm/s. The axial deformation of the soil increases with increasing CSR and seepage pressure. With an applied water pressure of 150 kPa at the bottom of the specimen and a CSR of 0.3, the maximum cumulative plastic strain reaches 4.78%, increasing by 53.2% compared with a CSR of 0.1. The hysteresis curve gradually becomes denser or thinner with increasing CSR and N; the hysteretic curve tends to a straight line for N of 5,000. The dynamic modulus increases with increasing N and depends on the CSR and seepage pressure. Empirical equations are suggested for calculating the dynamic modulus with different CSR values and seepage pressures. The results of this study can provide reference parameters for the construction and design of tunnels and subgrades of tidal flat areas in clay strata under the influence of water environments.